Technoeconomic assessment of hydrogen cogeneration via high temperature steam electrolysis with a light-water reactor. (15th January 2022) - Frick, Konor; Wendt, Daniel; Talbot, Paul; Rabiti, Cristian; Boardman, Richard
Highlights: "Carbon free" hydrogen can be made economic through integration with nuclear power plants. Nuclear based hydrogen production can be cost competitive with existing forms of hydrogen production. Through inclusion of hydrogen production, nuclear power plants can increase revenues. High Temperature Steam Electrolysis can act as an instant load follower to capture price peaks. Hydrogen storage is a vital part of maximizing market diversification. Abstract: Increased electricity production from renewable energy resources, coupled with low natural gas (NG) prices, has caused existing light-water reactors (LWRs) to experience diminishing returns from the electricity market. This reduction in revenue is forcing LWRs to consider alternative revenue streams, such as introduction hydrogen production or desalination, to remain profitable. This paper performs a technoeconomic assessment (TEA) regarding the viability of retrofitting existing pressurized-water reactors (PWRs) to produce green hydrogen (H2 ) via high-temperature steam electrolysis (HTSE). Such an integration would allow nuclear facilities to expand into additional markets that may be more profitable in the long term and eliminate CO2 emissions from the hydrogen production process. To accommodate such an integration, a detailed single market levelized cost of hydrogen (LCOH) and multimarket analyses were conducted of HTSE process operation, requirements, costing, and flexibility. Alongside this costing analysis, market analyses were conducted on the electric and hydrogen markets in the PJM interconnect. Utilizing a novel stochastic, dispatch optimization approach results suggest that a positive gain is achievable, and by operating in multiple markets, the nuclear facility can avoid the sale of electricity during times of low electricity market pricing, while maintaining the ability to capitalize on the high electricity market pricing. It should be noted that the analysis conducted is a differential cash flow analysis and, as such, does not present profit levels. LCOH analysis results demonstrate the potential exists to produce hydrogen at a cost as low as 1.20/kg. This price is lower than traditional steam methane reforming (SMR) allowing nuclear based hydrogen production to disrupt the existing hydrogen production market.